Pronunciation of Morphemes Containing Phoneme /r/ by Slurred Student in Universitas Klabat - B, Lumoindong (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Building communication between fellow humans was one of the ways to express one's identity. Built interactions can appear in various forms. One of the most commonly used forms of communication was conversation. In conversation, each person had different abilities. This ability was greatly influenced by several things, such as educational background, level of familiarity, purpose of conversation, and physical abilities of the parties involved. Regarding physical abilities, each person had advantages and disadvantages in interacting. One of the deficiencies that we often find was a person's inability to pronounce morphemes containing the phoneme /r/ so that sometimes the message to be conveyed cannot be understood properly by the person to whom the message was sent. This research was aimed at examining the problems faced by Klabat University students who suffer from slurred in pronouncing morphemes with the phoneme /r/, and what factors caused someone to suffer from slurred. The results of this study showed that people with slurred usually have experienced this problem since they were at an early age. Various efforts made to improve the ability of slurred sufferers to pronounce morphemes with the /r/ phoneme in them are known to have little effect in improving the sufferer's ability to pronounce this. Persecution which ultimately results in a decrease in learning achievement at school was also experienced by people with slurred.